Distinct genome‐wide methylation patterns in sporadic and hereditary nonfunctioning pancreatic neuroendocrine tumors. Issue 8 (8th January 2019) - Tirosh, Amit; Mukherjee, Sanjit; Lack, Justin; Gara, Sudheer Kumar; Wang, Sophie; Quezado, Martha M.; Keutgen, Xavier M.; Wu, Xiaolin; Cam, Maggie; Kumar, Suresh; Patel, Dhaval; Nilubol, Naris; et al.
Abstract : Background: Aberrant methylation is a known cause of cancer initiation and/or progression. There are scant data on the genome‐wide methylation pattern of nonfunctioning pancreatic neuroendocrine tumors (NFPanNETs) and sporadic and hereditary NFPanNETs. Methods: Thirty‐three tissue samples were analyzed: they included samples from sporadic (n = 9), von Hippel‐Lindau (VHL)‐related (n = 10), and multiple endocrine neoplasia type 1 (MEN1)–related NFPanNETs (n = 10) as well as normal islet cells (n = 4) for comparison. Genome‐wide CpG methylation profiling was performed with the Infinium MethylationEPIC BeadChip assay and was analyzed with R‐based tools. Results: In unsupervised hierarchical clustering, sporadic and MEN1‐related NFPanNETs clustered together, and the VHL group was in a separate cluster. MEN1‐related NFPanNETs had a higher rate of hypermethylated CpG sites in comparison with sporadic and VHL‐related tumor groups. Differentially methylated region analysis confirmed the higher rate of hypermethylation in MEN1‐related tumors. Moreover, in an integrated analysis of gene expression data for the same tumor samples, downregulated gene expression was found in most genes that were hypermethylated. In a CpG island methylator phenotype analysis, 3 genes were identified and confirmed to have downregulated gene expression: secreted frizzle‐related protein 5 ( SFRP5 ) in sporadic NFPanNETs and cell division cycle–associated 7‐like ( CDCA7L ) and RNA binding motif 47 ( RBM47 ) in MEN1‐related NFPanNETs. Conclusions: MEN1 NFPanNETs have a higher rate of geno me‐wide hypermethylation than other NFPanNET subtypes. The similarity between the pathways enriched in a methylation analysis of known genes involved in NFPanNET tumorigenesis suggests a key role for aberrant methylation in the pathogenesis of NFPanNETs. Abstract : There are scant data on the genome‐wide methylation pattern of sporadic and hereditary nonfunctioning pancreatic neuroendocrine tumors. The current analysis compares the genome‐wide methylome of nonfunctioning pancreatic neuroendocrine tumors in patients with and without hereditary syndromes, and it demonstrates a higher rate of hypermethylation in those tumors related to multiple endocrine neoplasia type 1 and hypomethylation in von Hippel‐Lindau–related tumors.